The impact of small-for-gestational-age Status on the outcomes in very-Low-birth-weight (VLBW) premature infants: a prospective cohort study in Taiwan - Lin, Chia-Ying; Chang, Hung-Yang; Chang, Jui-Hsing; Hsu, Chyong-Hsin; Jim, Wai-Tim; Peng, Chun-Chih; Chen, Chia-Huei (Frontiers in Pediatrics, 2023)
Background The impact of small-for-gestational-age (SGA) on very-low-birth-weight (VLBW) premature infants remains inconclusive. This study aimed to assess the effects of being born SGA status on the short-term and long-term outcomes in VLBW preterm infants. Methods We conducted a population-based, prospective cohort study on VLBW preterm infants born in Taiwan between 2012 and 2017. Sociodemographic, neonatal, growth and neurological data at 2 years of corrected age were collected. A total of 4243 VLBW infants born at 24 through 32 completed weeks' gestation participated in this study, of whom 1,005 had SGA status defined as a birth weight <10th percentile of gestation, and 3,238 did not (the non-SGA group). We compared the risks of short-term outcomes (neonatal mortality and morbidities), long-term outcomes (growth status, including weight, height, and head circumference <10th percentile, and neurodevelopmental impairments at 2 years of age). Subgroup analysis was performed by stratification of gestation age (GA): GA 24–26, 27–29 and 30–32 weeks. Results In the analysis of short-term outcomes, the SGA group had an increased risk of neonatal mortality [adjusted odds ratio (OR) = 2.66, 2.99, and 2.19, respectively] in all GA subgroups in comparison with the non-SGA group (p < 0.05). The SGA group had a significantly increased risk of bronchopulmonary dysplasia in GA 27–29 and 30–32 weeks (adjusted OR = 2.11 and 1.86, respectively). We also found that there was an increased risk of severe retinopathy of prematurity in GA 24–26 and 27–29 weeks in the SGA group compared with the non-SGA group (adjusted OR = 1.68 and 1.59, respectively). In the analysis of long-term outcomes, the SGA group had a significantly increased risk of NDI throughout all GA subgroups (adjusted = 1.94, 1.33, and 1.35, respectively) in comparison with the non-SGA group. The SGA groups also had an increased risk of growth status <10th percentile at 2 years of age (p < 0.05). Conclusions SGA VLBW premature infants had higher risks of neonatal death, growth status <10th percentile, and NDI at 2 years of corrected age compared with the non- SGA premature infants. Prenatal surveillance, postnatal attention, and long- term follow-up are warranted to improve the outcomes of VLBW SGA premature infants.